Fabrication and evaluation of novel non-enzymatic hydrogen peroxide and glucose sensors based on conducting polymer/nanocomposites / Pooria Moozarm Nia - Pooria, Moozarm Nia (2017)
This research utilized seven novel nanocomposites as non-enzymatic hydrogen peroxide (H2O2) sensor viz. glassy carbon electrode (GCE) as substrate. The composites were prepared with various combinations of polypyrrole (Ppy), reduced graphene oxide (rGO), copper and silver nanoparticles (CuNPs and AgNPs) via different electrodeposition processes. Sensors which were prepared by one-step electrodeposition of rGO-CuNPs and rGO-AgNPs showed a linear detection range up to 18 and 24 mmol.L-1, with LOD of 0.601 and 0.016 μmol.L-1, respectively towards H2O2. Their good performance is attributed to high surface area and synergetic effect of AgNPs and CuNPs with rGO. Polypyrrole was electrodeposited into the composite as a matrix on which nanometals could embed. The investigations revealed the type of dopants is highly effective in morphology and electrocatalytic performance of sensor. Polypyrrole was fabricated layer-by-layer electrodeposition method in the form of nanofiber when lithium perchlorate was used and showed the best performance. The synergetic effect of rGO, AgNPs and PpyNFs made (rGO-AgNPs)/PpyNFs composite an excellent H2O2 sensor with LOD of 1.099 μmol.L-1 with the wide linear range up to 90 mmol.L-1. Layer-by-layer electrodeposition of (rGO/PpyNFs/CuxO) led to a sensor which showed the best electrocatalytic response to H2O2 among all modified electrodes where LOD of 0.030 μmol.L-1 and wide linear range detection up to 100 mmol.L-1 were recorded. This electrode was further tested as amperometric glucose sensor and showed satisfactory performance with detection range of 0.038 μmol.L-1 at the same linear range, which enable it to be used for dual analytes detection. Therefore, along with sensing H2O2, this sensor was used as detector for glucose. To further look into the effect of rGO on sensor performance, PpyMTs-CuNPs and PpyNFs/AgNPs were prepared via one-step and layer-by-layer electrodeposition, respectively in the absence of rGO. PpyMTs-CuNPs electrode showed good response towards H2O2 with LOD of 0.900 μmol.L-1 and linear range up to 110 mmol.L-1, whereas PpyNFs/AgNPs showed good electroreduction response to H2O2 with LOD of 0.115 μmol.L-1 with detection range up to 120 mmol.L-1. It is believed the rGO wrinkle-like morphology was able to increase the surface roughness and consequently acted as an excellent underneath layer. Polypyrrole showed an excellent substrate as a suitable matrix for incorporating nanometals and enhanced speed, sensitivity, selectivity and versatility of the prepared sensors for H2O2 detection. Metal nanoparticles (AgNPs and CuNPs) exhibited a narrow size distribution, enhanced electrocatalytic activity and increased electrocatalytic selectivity with wide linear range and the detection of H2O2 at low potential. These unique properties of the silver and copper nanoparticles could be ascribed to their excellent electron transfer abilities as well as the ultra-high surface area derived from their nanoscale size.